Segmentation of quasi-stationarysignalportionsusing coefficientwaveform - Medetov, B.; Koyshigarin, A.; Baygozhina, A. (Recent Contributions to Physics, 2015)
This paperisdevoted to the developmenta new methodof segmentationin thequasi-stationarysignalportions.The authors ofproposedmethod of performingsegmentation ofthe signal at thequasi-stationaryareas.As thesignal is consideredspeech.A review ofexisting methods forautomatic segmentationof the fusedspeech signalinto its componentelements, in accordance with thephonetic transcriptionof the language .A comparative analysis of the proposed method with other methods known. On the basis of this analysis, it is concluded that the proposed new method, which uses the coefficientwaveform gives the best results.